2021
DOI: 10.3390/ijgi10040213
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of ‘Glyphmaps’ for Analysing the Scale and Temporal Spread of COVID-19 Reported Cases

Abstract: Recent analysis of area-level COVID-19 cases data attempts to grapple with a challenge familiar to geovisualization: how to capture the development of the virus, whilst supporting analysis across geographic areas? We present several glyphmap designs for addressing this challenge applied to local authority data in England whereby charts displaying multiple aspects related to the pandemic are given a geographic arrangement. These graphics are visually complex, with clutter, occlusion and salience bias an inevita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Instead we generate a graphical line‐up test (Buja et al, 2009) where the observed data is hidden among a set of decoy plots of the same data, but with RR values randomly permuted across local authorities. Such tests have particular utility in geographical analysis (Widen et al, 2016; Beecham et al, 2021), as there is a tendency to over‐interpret geographic structure represented in map designs (Klippel, Hardisty, and Li, 2011; Doppler et al, 2021). Since the docoy plots are constructed based on a random allocation, the line‐up test in Fig.…”
Section: Applicationmentioning
confidence: 99%
“…Instead we generate a graphical line‐up test (Buja et al, 2009) where the observed data is hidden among a set of decoy plots of the same data, but with RR values randomly permuted across local authorities. Such tests have particular utility in geographical analysis (Widen et al, 2016; Beecham et al, 2021), as there is a tendency to over‐interpret geographic structure represented in map designs (Klippel, Hardisty, and Li, 2011; Doppler et al, 2021). Since the docoy plots are constructed based on a random allocation, the line‐up test in Fig.…”
Section: Applicationmentioning
confidence: 99%
“…These approaches could be used to co-visualize the spatial distribution of event data, enabling the identification of structures. For example, some of them have already been used specifically for COVID-19 data, such as glyph-based representations (Beecham et al, 2021, Lan et al, 2021 and 3D representations (Lan et al, 2021). However, temporal animation is not considered as the best option for the visual exploration of spatio-temporal data (Harrower et al, 2008), and the use of small multiples or integrated diagrams in 2D representations can be problematic in case of a high number of timesteps or spatial locations to covisualize (Davoine et al, 2015).…”
Section: The Role Of Map Design For the Visual Identification Of Structures In Event Data Distributionmentioning
confidence: 99%
“…Gridmaps, sometimes called tilemaps, are maps where spatial units form grid cells of regular size, allocated into an approximate spatial arrangement. The advantage is that complex multivariate structure, rather than single values, can be depicted (Beecham and Slingsby, 2019;Beecham et al, 2020) and tested (Wood et al, 2011;Beecham et al, 2021) within geographic context. Many gridmaps are generated manually, the widely used LondonSquared layout of London boroughs (After the Flood, 2019) or those made available via the geofacet package (Hafen, 2024).…”
Section: Introductionmentioning
confidence: 99%